Synthesis and self‐assembling of poly(N‐isopropylacrylamide‐block‐poly(L‐lactide)‐block‐poly(N‐isopropylacrylamide) triblock copolymers prepared by combination of ring‐opening polymerization and atom transfer radical polymerization. Issue 15 (16th May 2013) - Hu, Yanfei; Darcos, Vincent; Monge, Sophie; Li, Suming
ABSTRACT Novel thermo‐responsive poly(N‐isopropylacrylamide)‐block‐poly(l‐lactide)‐block‐poly(N‐isopropylacylamide) (PNIPAAm‐b‐PLLA‐b‐PNIPAAm) triblock copolymers were successfully prepared by atom transfer radical polymerization of NIPAAm with Br‐PLLA‐Br macroinitiator, using a CuCl/tris(2‐dimethylaminoethyl) amine (Me6TREN) complex as catalyst at 25 °C in a N, N‐dimethylformamide/water mixture. The molecular weight of the copolymers ranges from 18, 000 to 38, 000 g mol−1, and the dispersity from 1.10 to 1.28. Micelles are formed by self‐assembly of copolymers in aqueous medium at room temperature, as evidenced by 1H NMR, dynamic light scattering (DLS) and transmission electron microscopy (TEM). The critical micelle concentration determined by fluorescence spectroscopy ranges from 0.0077 to 0.016 mg mL−1. 1H NMR analysis in selective solvents confirmed the core‐shell structure of micelles. The copolymers exhibit a lower critical solution temperature (LCST) between 32.1 and 32.8 °C. The micelles are spherical in shape with a mean diameter between 31.4 and 83.3 nm, as determined by TEM and DLS. When the temperature is raised above the LCST, micelle size increases at high copolymer concentrations due to aggregation. In contrast, at low copolymer concentrations, decrease of micelle size is observed due to collapse of PNIPAAm chains. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2013, 51, 3274–3283